Measuring school engagement for child welfare involved youth: Assessing the dimensionality of the Drug Free School Scale. (June 2019) - Cage, Jamie; Yoon, Susan; Barhart, Sheila; Coles, Crystal; McGinnis, Hollee A.; Starns, Abigail L.
Abstract: Background: Research using data from the National Survey of Child and Adolescent Well-Being (NSCAW) have consistently used the scale developed from the Drug Free Schools and Communities Act (DFSCA) to examine school engagement. Although the DFSCA is widely used, no study has examined the factor structure to determine if the scale is best used as a summative score of all items or as a three-factor variable distinguishing behavioral, emotional, and cognitive school engagement. Objective: The primary goal of this study was to evaluate the hypothesized factor structure of the DFSCA scale by testing models previously supported in the literature. Methods: Using NSCAW-I data, we performed confirmatory factor analysis in a structural equation modeling (SEM) framework. Participant: The study sample included 2429 children and adolescents who were between 6 and 15 years of age who had recently been investigated by child protective services due to a maltreatment report. Results: Results indicated that school engagement is a multidimensional concept measuring behavioral, emotional, and cognitive-behavioral dimensions. This model has not been used in studies using NSCAW data, to date. These findings highlight the importance of exploring and understanding the factor structure of instruments before using an instrument in studies.